The Emotional Underpinnings of Populism: How Anger and Fear Affect Populist Attitudes. Issue 4 (22nd August 2017) - Rico, Guillem; Guinjoan, Marc; Anduiza, Eva
Abstract: Popular accounts of populist movements often point to negative emotions as a key motivating factor underlying their support. However, little systematic research has been devoted to examining differences in how distinct negative emotions affect levels of populism among voters. This paper attempts to fill this gap by focusing on the influence of the two emotions most frequently connected to populism in political commentary: fear and anger. Informed by appraisal theories of emotions, we hypothesize that populist attitudes are driven by feelings of anger, rather than fear. Using a three‐wave online panel survey of Spanish citizens between 2014 and 2016, we find that anger expressed over the economic crisis is consistently associated with variations in support for populism both between individuals and over time, whereas no significant effects emerge for expressions of fear. We discuss the implications of these findings for understanding the nature of populist support.